A Numerical Discussion about Willem De Sitter Cosmological Model: Exploring the behavior of the electromagnetized Willem De Sitter cosmological model (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper we will investigate a numerical discussion about Williem sitter cosmological model filled with an electro magnetized with Nambu strings in general relativity. Here we assume that in electromagnetic field tensor Eij, E23 is the only non-vanishing component. Under the assumption that the expansion θ in the model is proportional to the shear σ which leads to N = Mn (where M and N are functions of time only). Also we will discuss the cosmological model physical behavior.